Foetal loss after chorionic villus sampling and amniocentesis in twin pregnancies: A multicentre retrospective cohort study. (27th September 2022) - Navaratnam, Kate; Khairudin, Delima; Chilton, Robyn; Sharp, Andrew; Attilakos, George; Stott, Daniel; Relph, Sophie; Spencer, Rebecca; Badr, Dominique A.; Carlin, Andrew; Jani, Jacques; Kilby, Mark D.; et al.
Abstract: Objective: We aimed to determine foetal losses for DCDA and MCDA twins following transabdominal CVS or amniocentesis performed <22+ 0  weeks. Methods: Retrospective cohort study conducted in the UK and Belgium 01/01/00–01/06/20. Cases with unknown chorionicity, monochorionic complications or complex procedures were excluded. Uncomplicated DCDA and MCDA twins without invasive procedures were identified as controls. We reported foetal losses <24+ 0  weeks and losses of genetically and structurally normal foetuses. Results: Outcomes were compared for DCDA foetuses; 258 after CVS with 3406 controls, 406 after amniocentesis with 3390 controls plus MCDA foetuses, 98 after CVS with 1124 controls, and 160 after amniocentesis with 1122 controls. There were more losses <24+ 0  weeks with both procedures in DCDA (CVS RR 5.54 95% CI 3.38–9.08, amniocentesis RR 2.36 95% CI 1.22–4.56) and MCDA twins (CVS RR 5.14 95% CI 2.51–10.54, amniocentesis RR 7.01 95% CI 3.86–12.74). Losses of normal foetuses were comparable to controls (DCDA CVS RR 0.39 95% CI 0.05–2.83, DCDA amniocentesis RR 1.16 95% CI 0.42–3.22, MCDA CVS RR 2.3 95% CI 0.71–7.56, and MCDA amniocentesis RR 1.93 95% CI 0.59–6.38). Conclusions: This study indicates increased foetal losses for DCDA and MCDA twins following CVS and amniocentesis with uncertain risk to normal foetuses. Key points: What's already known about this topic? Monochorionic twins are at a higher baseline risk of foetal loss, but outcome data for these pregnancies following CVS and amniocentesis are limited. Procedure‐related losses following CVS and amniocentesis in twins overall may be lower than previously reported. Procedures themselves may not contribute significantly to pregnancy loss for women at a higher baseline risk but may be more influential for women at lower a priori risk. What does this study add? Spontaneous losses of twins prior to 24 weeks are increased after CVS and amniocentesis for both DCDA and MCDA pregnancies compared to controls. Losses of structurally and genetically normal twins appear comparable to control groups. However, due to low numbers of adverse outcomes in our cohort and other published analyses, further evidence is required. Maternal counselling should highlight different baseline risks between MCDA and DCDA twins and the contribution of maternal and pregnancy factors to outcomes for complex twin pregnancies.